Multiphysics Implementation of Electrokinetic Remediation Models for Natural Soils and Porewaters. (20th January 2017) - López-Vizcaíno, R.; Yustres, A.; León, M.J.; Saez, C.; Cañizares, P.; Rodrigo, M.A.; Navarro, V.
Graphical abstract: Highlights: A conceptual and numerical model for electrokinetic soil remediation is presented. A simplified and an extended geochemical system are compared. The influence of the natural porewater composition on the pH variation is shown. Abstract: Models of electrokinetic soil remediation systems have been developed significantly in recent decades. A wide range of physicochemical phenomena occurs in this type of process, which makes it difficult to capture all of the system's complexity in a model. Therefore, existing models do not attempt to simulate the behaviour of the entire geochemical system of natural soils and their porewaters but rather focus on the pollutant compounds of interest. This paper proposes a conceptual and numerical model that includes geochemical speciation other than the phenomena that have been described by other authors. In addition, a comparative modelling exercise is performed with a composition of natural porewater and a simplified equivalent composition. The results show that the buffering system of carbonates affects the temporal evolution and spatial distribution of the pH. Because the pH controls many of the phenomena that occur during this type of remediation, simulations using realistic geochemical systems are critical.